2013
DOI: 10.1016/j.biopsych.2013.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association Study Identifies New Susceptibility Loci for Posttraumatic Stress Disorder

Abstract: Background Genetic factors influence the risk for posttraumatic stress disorder (PTSD), a potentially chronic and disabling psychiatric disorder that can arise after exposure to trauma. Candidate gene association studies have identified few genetic variants that contribute to PTSD risk. Methods We conducted genome-wide association analyses in 1578 European Americans (EAs), including 300 PTSD cases, and 2766 African Americans, including 444 PTSD cases, to find novel common risk alleles for PTSD. We used the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
125
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 159 publications
(132 citation statements)
references
References 40 publications
3
125
2
2
Order By: Relevance
“…However, the association of rs6812849 in TLL1 (Xie et al, 2013) was originally detected in a larger study, and rs10170218 in LINC01090 (Guffanti et al, 2013) was originally found in an all-female AA cohort, which was also larger than the all-male MRS AA cohort, and MRS findings for these genes remain inconclusive.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…However, the association of rs6812849 in TLL1 (Xie et al, 2013) was originally detected in a larger study, and rs10170218 in LINC01090 (Guffanti et al, 2013) was originally found in an all-female AA cohort, which was also larger than the all-male MRS AA cohort, and MRS findings for these genes remain inconclusive.…”
Section: Discussionmentioning
confidence: 97%
“…We also compiled a list of genes that have been reported in the literature to be significantly associated with PTSD, either showing a main effect for the genetic marker, and/or a significant GxE interaction (Amstadter et al, 2009(Amstadter et al, , 2011Binder et al, 2008;Boscarino et al, 2011;Cao et al, 2013;Comings et al, 1996;Dragan and Oniszczenko, 2009;Gillespie et al, 2013;Goenjian et al, 2012;Grabe et al, 2009;Guffanti et al, 2013;Hauer et al, 2011;Kolassa et al, 2010;Logue et al, 2013a,b;Lyons et al, 2013;Mellman et al, 2009;Nelson et al, 2009;Ressler et al, 2011;Segman et al, 2002;Solovieff et al, 2014;Voisey et al, 2010;Wilker et al, 2013;Xie et al, 2013). Since most studies were performed in subjects of either European or African descent, we used these specific ancestry groups for comparison with MRS. We found that most of the 25 candidate genes showed nominally significant associations in MRS for at least one of the SNPs tested.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations